Perjalanan Rohani Perspektif Kaum Sufi - Adnan Adnan (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2017)
Sufism as a spiritual life was frequently to be a return place for the tired man because of his life journey and an escape place for the pressed man. Beside that, actually sufism can strengthen the week individuals missing his self-existance. By sufism, they found the real meaning of life. In the teachings of sufi order, the seeker (salik) has to pass through spiritual path (thariqah) in order to know Allah as the Final Goal by passing a long journey and spiritual stations (maqamat) to improve their bad characteristics. This is significant to do for salikin, especially to make his inner empty, and then adorn and decorate it with all of good characteristics to reach higher and higher stations (maqamat). In the other hand, they found a religious-psycological experiences which is called ahwal to achive the spiritual experiences with Divine Reality (Haqiqah).